The role of fuel cost information in new car sales. (September 2019) - Brazil, William; Kallbekken, Steffen; Sælen, Håkon; Carroll, James
Highlights: Information failure is a barrier to adoption of low-carbon vehicles. Including fuel costs on car labels increases WTP for fuel-efficient vehicles. Adding fuel costs to EU labels could help reach political goals. Abstract: Transitioning to more sustainable transport behaviours is key to achieving national and international climate change objectives. Households can contribute to the new low carbon economy by switching to more energy efficient vehicles. In addition to societal and environmental benefits, such a change should lead to private benefits for households through lower energy expenses, while avoiding the perceived costs that could accompany a modal change in personal transportation (switching away from cars). This paper uses a discrete choice experiment (stated preference) to explore the effects of using alternative fuel cost labels on the demand for more efficient cars. Results show that reframing from fuel consumption (litres) to monthly fuel costs increases the willingness to pay for higher levels of fuel efficiency. More generally, these results highlight that informational interventions can be improved by framing information in a metric that is more salient and familiar to consumers.